Health Academy Program: importance for users and funding difficulties - Ana Mônica Serakides Ivo; Vinicius Coimbra Viana; Maria Imaculada de Fátima Freitas (Revista Brasileira de Atividade Física e Saúde)
The Health Academy Program (PAS) is a public health promotion policy in primary care (PC) that has physical activity (PA) as one of its main axes. The Previne Brasil Program (PPB) established a new funding program for PC in 2019. The aim of this study was to understand the meaning of PA and PAS according to its users and to discuss the consequences of PPB in the structuring and functioning of the program. This is a qualitative approach study, supported by the theory of social representations. 33 in-depth interviews were performed on users from the Belo Horizonte PAS, interpreted by the Structural Narration Analysis. It was revealed that there are profound representations on PA as remedy for physical and psychosocial diseases and others, such as a contribution for the improvement of quality of life. Users see PAS as a necessary and inclusive health promotion policy, as it offers free access to quality PA, defined as one of the main aspects for joining it. The funding provided from the PPB does not include specific funding for team maintenance for the Extended Nucleus of Family Health in Primary Care, removing responsibility from the municipal managers to gather multiprofessional teams. The absence of these teams, which include physical education professionals who are responsible for 90% of the actions of the PAS, can compromise the outcomes recognized by the users of the program, especially those related to the reduction of inequalities of access and also the various actions to promote health within the PC.